Sadder but wiser: Emotional reactions and wisdom in a simulated suicide intervention. (5th October 2018) - Hu, Chao S.; Huang, Jinhao; Ferrari, Michel; Wang, Qiandong; Xie, Dong; Zhang, Haotian
Abstract : Scholars within the Berlin paradigm have analysed participants' responses to a hypothetical vignette about a friend's suicide ideation. However, no study has yet focused on participants' emotional reactions to this scenario, an important aspect of wisdom performance. We conducted a Thin‐Slice Wisdom study where participants were asked to give advice to a hypothetical friend contemplating suicide. We analysed their emotional profiles using facial expression analysis software (FACET2.1 and FACEREADER7.1). Participants' verbal responses were also transcribed and then scored by 10 raters using the Berlin criteria. Results revealed that the sadder the participants felt, the wiser their performance. Wiser participants may have been better at exploring this sad, but true, existential human dilemma.